Aktivitas Digital dan Internalitas Religius Penghafal Al-Qur’an Generasi Z di Era Media Sosial - Asykriyah Laily Rizki; Nasrulloh (Al-Kindi, 2026)
This study aims to analyze the digital activities of Generation Z Quran memorizers and their influence on religious internality in the social media era through the perspective of the hadith of the Prophet Muhammad SAW. Generation Z as digital natives live in two spaces at once: Islamic boarding schools that demand spiritual tranquility and a fast, interactive, and distraction-filled digital space. The study uses a qualitative phenomenological approach with data collection through observation and in-depth interviews with tahfiz students aged 15–25 years. The results show that digital activities have a dual impact: expanding religious literacy and memorization motivation, but also triggering distraction, decreasing focus on murojaah, and disrupting the solemnity of worship. Religious internality, which includes sincerity, trustworthiness, commitment to worship, and self-control, plays an important role in maintaining the spiritual stability of students. The hadith regarding the Prophet's uswah ḥasanah has proven to be a guideline for media ethics, especially in verifying information, guarding speech, and displaying Quranic morals in the digital space. This research confirms that digital technology is not only a challenge, but can be a means of forming religious identity if managed based on prophetic values.